Economic determinants of unemployment in Malaysia / Siti Rahmah Halimulpata - Halimulpata, Siti Rahmah (Faculty of Business Management, 2014)
Unemployment is a serious problem that may affect to the developed economies. Malaysia is one of the country will face the challenge of unemployment. This paper aims to investigate the effect of economic variables to the unemployment rate in Malaysia. The variables considered are population, inflation and exchange rate. The sample of this study comprises the observations of the independent and dependent variables on a yearly basis over 30 years from 1984 to 2013. The data will collect from World Data Bank or International Monetary Fund,World Data Atlas – Knoema and Index Mundi. The data mostly is collect from the website. This research paper is used a secondary data. It also will use the time series data. The data are collected then compiled by using E-Views7. The software mayhelp to determine the descriptive analysis, stationary test, correlation analysis, regression analysis and test on assumption (autocorrelation, normality test, heteroscedascity, multicollinerity and ramsey reset test). The study is an attempt to investigate the relationship of the chosen economic variables towards influencing unemployment rate in Malaysia. Findings from previous research papers mostly may help this research have been done that give a lot of information. The results of this research paper may make a conclusion for the research project paper.